Penggunaan Skor CONUT untuk Penentuan Pasien Stroke Iskemik - Agustiawan; Dewi Novita; Ayu Meilina (Cermin Dunia Kedokteran, 2024)
Stroke patients are vulnerable to malnutrition, which is associated with poor outcomes, both in the acute and rehabilitation phases. Malnutrition at admission and one week after admission is a predictor of poor outcomes within or after three months of stroke. Adequate nutritional assessment and management are necessary to improve the outcomes of stroke patients. The CONUT score can be used for nutrition assessment in stroke patients.